2008
DOI: 10.1038/ijo.2008.205
|View full text |Cite
|
Sign up to set email alerts
|

The time course of salt-induced hypertension, and why it matters

Abstract: The epidemiology of salt-induced hypertension has been explored in detail in animal studies, in some cases involving exposures to excess dietary salt for much of the animal's lifespan. The results of these studies demonstrate the presence of two distinct time courses of the blood pressure response to a high salt intake: an acute (rapid) blood pressure response occurring over days to weeks, and a slow and progressive blood pressure response that develops over extremely long periods of time, amounting to a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 88 publications
0
30
1
1
Order By: Relevance
“…4,69 The effects of excess sodium intake on blood pressure can be both short-term and cumulative and long-lasting, in keeping with the higher prevalence of hypertension among older people, as shown in meta-analyses and global observational studies such as INTERSALT. 3,58,59 In addition, physiological studies in animals and humans indicate that sodium reduction could reduce cardiovascular risk through mechanisms independent of blood pressure, such as improved endothelial functioning, decreased arterial stiffness, and decreased left ventricular mass. 60 …”
Section: Coherencementioning
confidence: 99%
“…4,69 The effects of excess sodium intake on blood pressure can be both short-term and cumulative and long-lasting, in keeping with the higher prevalence of hypertension among older people, as shown in meta-analyses and global observational studies such as INTERSALT. 3,58,59 In addition, physiological studies in animals and humans indicate that sodium reduction could reduce cardiovascular risk through mechanisms independent of blood pressure, such as improved endothelial functioning, decreased arterial stiffness, and decreased left ventricular mass. 60 …”
Section: Coherencementioning
confidence: 99%
“…High dietary salt intake is an environmental factor linked with increased blood pressure and cardiovascular and renal injury [41,45]. A variety of mechanisms have been suggested to contribute to salt induced changes in blood pressure and cardiovascular function.…”
Section: Introductionmentioning
confidence: 99%
“…At the other extreme, high dietary salt intakes have also been demonstrated to affect BP on a much slower time scale of many months or years [9-12]. In some studies, these slow and progressive effects of salt have been found to be partly irreversible [13-15], the irreversible characteristic corresponding with a shift of the chronic pressure natriuresis relationship to higher BP levels [13,14]. Finally, an effect of sustained salt loading to alter the slope of the chronic pressure natriuresis relationship, amounting to a salt induced worsening of acute salt-sensitivity, has also been suggested [13,14].…”
Section: Introductionmentioning
confidence: 99%